Distilled liquid smoke coconut shell attenuates the cytokine profile of macrophages in oral ulcer in experimental model of diabetes mellitus - Meircurius Dwi Condro Surboyo, Diah Savitri Ernawati, Desiana Radithia, Bagus Soebadi, Fatma Yasmin Mahdani, Nurina Febriyanti Ayuningtyas, Fiona Cherrilia Adji, Novia Ambar Larasati (Journal of Applied Pharmaceutical Science, 2021)
The effects of distilled liquid smoke coconut shell (DLS-CS) on the macrophages and nuclear factor erythroid2-related factor 2 (Nrf2) and cytokine profiles, that is, tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β), were analyzed in oral ulcer tissues affected by diabetes mellitus. Wistar rats were injected with alloxan to create diabetes mellitus, and an oral ulcer was made in the inferior labial fornix mucosa. The rats were treated with DLS-CS 20 µl/20 g body weight, topically, once a day for 3, 5, and 7 days. The Nrf2, TNF-α, IL-6, and IL-1β profiles were analyzed with immunohistochemistry staining and the macrophage count with hematoxylin-eosin staining. The Nrf2 profile was increased after 5 days of treatment and the IL-1β profile was consistently decreased (p < 0.05). The IL-6 profile started to decrease after 5 days, while the macrophages increased after 3 and 5 days. No significant difference was found in TNF-α expression. DLS-CS proved effective in decreasing IL-6 and IL-1β profiles as well as increasing Nrf2 and macrophage migration in oral ulcers with diabetes mellitus.
Keywords: Distilled liquid smoke coconut shell, oral ulcer, diabetes mellitus, proinflammatory cytokines, macrophages